Effect of Urea Fertilization on Agronomic Characteristics and Biomass Yield of Hydroponic Maize Fodder - Gashu, Negesse; Kechero, Yisehak; Tadele , Yilkal (Journal of Cereal Research, 2023)
The objective of this experiment was to investigate the effect of urea treatment on the agronomic characteristics, biomass yield, and its economic feasibility of hydroponic maize fodder grown in a low-cost hydroponic production unit at Arba Minch University’s College of Agricultural Science The hydroponic unit was constructed from locally available materials and 500 grams of maize seeds were planted at the plastic trays at 7.6kg/m2 seeding rate. For the experiment the known maize seed (BH-540) variety was used. The five level of urea treatments composed of T1 (control), T2 (0.5 % urea), T3 (1.0% urea), T4 (1.5% urea) and T5 (2.0% urea) groups were applied in completely random design (CRD). Urea solution at different levels in the corresponding treatment groups was sprinkled daily two times (at 1 o’clock morning and evening local time) for a total period of 8 days and attributes of agronomic characteristics and biomass yield were recorded at the 9th day of growth. The collected data were analysed using the general linear model of SAS version 9.0 and presented with tables. Among the different treatments T2 group had a higher significant effect (p<0.05) and proven to be greater for leaf number (3.56±0.02), leaf area index (9.92±0.33 cm2), plant height (22.06±0.52 cm), shoot to root ratio (1.07:1.65), biomass yield (2710±94.34 grams/tray), seed to feed ratio (1: 5.42 kg) and dry biomass yield (0.46±0.02 kg/tray) of hydroponic maize. The lowest values were noticed in the T5 group; leaf number (2.64±0.18), leaf area index (3.30±0.18 cm2), plant height (10.74±0.85 cm), shoot to root ratio (0.40:1.13), biomass yield (1530±167.33 grams/tray), seed to feed ratio (1:3.06) and dry yield (0.31±0.03 kg/tray) of hydroponic maize. Urea application at 0.5% concentrations is optimum for hydroponic maize production as it is believed to favour the cell division, maintains the higher auxin and cytokinins levels which stimulate the cell elongation along the main axis leading to better growth and biomass yield of hydroponic maize fodder. Key words: Biomass Yield, Hydroponics, Maize Fodder, Nutritional Composition, Urea